UNSUR SUFISME DALAM KONSEP PENDIDIKAN SAID NURSI - Muhammad Faiz (Nizham Jurnal Studi Keislaman, 2015)
The concept of education according to Said Nursi’s view is an integration of three main elements or subjects which combine religious sciences (al-ulum al-diniyah), science of universe and modern technology (al-ulum al-kauniyah al-haditha) and the values of sufism doctrine. Nursi stated that religious knowledge is the light for heart and modern science is the light of the mind, a combination of both will guide to the truth and minimize the fanaticism and intellectual confusion. The main curriculum of learning that used is the study of the main topics contained in the Risale-i Nur. This concept will combine three holistic manners: spirituality from the religious schools (medrese), science and technology from the secular schools (mekteb) and morality from the sufistic schools (tekke).